KRITIK SOSIAL PERANG DALAM LIRIK LAGU IWAN FALS DAN BOB DYLAN - Fernando, Riki; WS, Hasanuddin; Hayati, Yenni (Jurnal Bahasa dan Sastra, 2018)
This thesis aims to describe the form of social criticism of war in song lyric of Iwan Fals and Bob Dylan and the comparation of them. This thesis belongs to qualitative research. Subject of this research is song lyric of Iwan Fals from www.iwanfals.co.idÂ and song lyric of Bob Dylan from www.bobdylan.com. The research focused to songlyricthat contains social criticism of war theme and applied to comparative literature theory. The method to analyze this data is descriptive analysis. Validity of data obtained by triangulation technique. Based on the results of the study concluded the following points. First, social criticism of war in song lyric of Iwan Fals described by persuade form. Second, social criticism of war in song lyric of Bob Dylan described by curse form. Third, sosial criticism of war in song lyric of Iwan Fals and Bob Dylan described by different form because different orientation: Iwan Fals tendents to push foward persuade form because war is only an useless, meanwhile Bob Dylan tendents to push foward curse form because war is very cruel.Keywords: song lyric, social criticism, comparative literature